Studi Gender Dimasa Remaja Dalam Kajian Bimbingan Penyuluhan Islam - Fatra, Edi; Subhi, Muhamad Rifai (Equalita: Jurnal Studi Gender dan Anak, 2023)
ABSTRACT: Adolescence is a period when children move towards adulthood. During adolescence, a person experiences physical, mental and social development. Development during adolescence is a development that is sensitive to new things. They are more likely to be able to adapt to something that is easy to do and have the freedom which today is much influenced by the outside world. The problem that most often occurs in adolescence is sexuality. Adolescents carry out deviant actions so that they experience these problems which result in the reproductive system being disrupted. Many diseases attack the reproductive system such as syphilis, gonorrhea, Chlamydia, HIV and AIDS. Teenagers need to be able to recognize this disease and how to prevent it with the contribution of good education. Currently, the curriculum used is the Merdeka learning curriculum at the Merdeka campus which is expected to contribute to preventing Triad-KRR. The Merdeka campus Merdeka learning curriculum uses a learning system that is free and easy to learn in accordance with adolescence. In these prevention efforts, gender roles are the main factor in preventing Triad-KRR. Differences between men and women are not an obstacle in this effort. This research method uses qualitative methods which deepen these problems. With this research, it is hoped that gender and education during adolescence can be controlled and structured well so that teenagers are not vulnerable to experiencing social deviation. The educational curriculum must be an effort to prevent gender-oriented Triad-KRR in adolescenceKeywords: Curriculum; Teenager; Triad-KRR; Gender